Combined Effect of Surface Roughness and Slip Velocity on Jenkins Model Based Magnetic Squeeze Film in Curved Rough Circular Plates. (3rd December 2014) - Patel, Jimit R.; Deheri, Gunamani
Abstract : This paper aims to discuss the effect of slip velocity and surface roughness on the performance of Jenkins model based magnetic squeeze film in curved rough circular plates. The upper plate's curvature parameter is governed by an exponential expression while a hyperbolic form describes the curvature of lower plates. The stochastic model of Christensen and Tonder has been adopted to study the effect of transverse surface roughness of the bearing surfaces. Beavers and Joseph's slip model has been employed here. The associated Reynolds type equation is solved to obtain the pressure distribution culminating in the calculation of load carrying capacity. The computed results show that the Jenkins model modifies the performance of the bearing system as compared to Neuringer-Rosensweig model, but this model provides little support to the negatively skewed roughness for overcoming the adverse effect of standard deviation and slip velocity even if curvature parameters are suitably chosen. This study establishes that for any type of improvement in the performance characteristics the slip parameter is required to be reduced even if variance (−ve) occurs and suitable magnetic strength is in force.